Toxicology of carbon nanomaterials in the Caenorhabditis elegans model: current status, characterization, and perspectives for testing harmonization - Côa, Francine; Bortolozzo, Leandro de Sá; Ávila, Daiana Silva; Souza Filho, Antonio G.; Martinez, Diego Stéfani Teodoro (Frontiers in Carbon, 2023)
Carbon nanomaterials are promising advanced materials for novel technologies. Therefore, biosafety studies are mandatory to support their safe development, uses, and disposal in sustainable innovation. Traditional toxicological assays are typically expensive, time-consuming, and have low throughput; they have been replaced by new approach methodologies (NAMs) focused on in vitro, in chemico and in silico approaches, along with alternative models. Caenorhabditis elegans has emerged as a complete model organism for predictive toxicology due to its transparent body, short reproductive and life cycles, and fully sequenced genome with high homology with the human genome. In this review, we discuss the current status, state-of-the-art characterization techniques, and scientific gaps in nanotoxicity studies involving the carbon nanomaterials and the C. elegans model considering the last two decades of research. Moreover, we show the existing supportive tools to evaluate the internalization and biodistribution of carbon nanomaterials in C. elegans and discuss their advantages and limitations. Methodological and experimental gaps must still be discussed with the scientific community; hence, we bring this discussion to light and point out future orientations and perspectives. This review will contribute for guiding the research with C. elegans and harmonization of assays/protocols linked to computational tools and nanoinformatics approaches during the development of carbon nanomaterials.